If God still breathes, why can't I?: Black Lives Matter and biblical authority - Parker, Angela N. (William B. Eerdmans Publishing Company, 2021)
Introduction: What is your relationship to the Bible? -- Stifled breathing : trained to be a white male biblical scholar -- White supremacist authoritarianism is not God's breath -- Stop gaslighting me -- Moving from stifled breath to full-throated faith -- Conclusion: Breathing womanist air.